Teachers’ Strategies to Motivate Young Learners in Learning English at Elementary School - Nadia Asyura; Meristika Moetia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This systematic literature review investigates teachers' motivational strategies and their associated implementation challenges in Teaching English to Young Learners (TEYL) within Indonesian primary education. To address the need for updated evidence-based synthesis, this study systematically analyzed 10 empirical research articles published in 2025 focusing on primary school contexts (Grades 1–6) in Indonesia. Guided by Braun and Clarke's (2006) six-phase thematic analysis framework, the synthesis yielded two primary findings. First, to enhance student motivation (RQ1), primary EFL teachers predominantly employ four pedagogical strategies: gamified and play-based learning, kinesthetic-auditory activities (TPR and songs), digital media integration, and contextual storytelling. Second, the implementation of these strategies (RQ2) is constrained by key operational and affective barriers, notably the lack of specialized TEYL teacher qualifications, student language anxiety, restricted instructional time, facility disparities, and mixed-ability classroom dynamics. The study underscores that optimizing young learners' English motivation requires an alignment of teacher pedagogical training, adequate instructional resources, and a supportive learning environment.